MOLECULAR SCREENING OF FXI DEFICIENCY GENE FRAGMENT IN NILI-RAVI BUFFALO BULLS OF PUNJAB, PAKISTAN - K. Zahra; M. Y. Zahoor; M. Imran; K. Ashraf; A. Nadeem; I. Rashid; Habib-ur-Rehman; K. Hassan; M. Younas; M. Akhtar; W. Shehzad (Journal of Animal and Plant Sciences, 2019)
Nili-Ravi buffalo breed has an immense potential for productivity and can be a part of effective breeding programs. However, with only a few reports detailing the genetic diseases of the breed, the burden such diseases place on it remains poorly evaluated. Buffalo populations can be afflicted with autosomal recessive disorders that require genetic screening to be detected and prevented. One such disease, Bovine plasma thromboplastin (Factor XI) deficiency, has been well documented in cattle breeds from all over the world. Screening for this disease in native Pakistani buffalo breed was carried out to evaluate its occurrence in the breeding sires. In this regard, blood samples were randomly collected from the breeding buffalo bulls (n=152) reared at Government owned buffalo farms in the Punjab Province. Subsequently, whole genomic DNA extraction followed by PCR amplification of FXI gene was carried out. The resulting 244 bp PCR product was sequenced by the Sanger method. No carriers were detected among the studied population. It is proposed that extensive screening of this disorder is required in the country in order to develop a complete picture of its molecular epidemiology. This study holds the merit of first report on Nili-Ravi buffalo FXI gene mutational screening from Pakistan.
Keywords: recessive traits; FXI deficiency; Nili-Ravi buffalos